Political Rhetoric and the Media The Year in C-SPAN Research, Volume 8 - Browning, Robert X. (Purdue University Press, 2022)
This volume of The Year in C-SPAN Archives Research features analyses of the C-SPAN Video Library, a digital collection of 275,000 hours of indexed videos, texts, and spoken words. Included in this volume are papers on Rev. Jesse Jackson's presidential campaign, rhetorical analysis of agriculture policy, and an examination of Senator Edward Kennedy's positions on health care. The text also contains analysis of the "spectacle of committee hearings" and a look at the visuals used in the second Trump impeachment trial.